Procedings of the 1st ICA Regional Conference, ICA 2019, October 16-17 2019, Bali, Indonesia 2021
DOI: 10.4108/eai.16-10-2019.2304286
|View full text |Cite
|
Sign up to set email alerts
|

The Discipline of Verification in a News Production Process (News Coverage of the Polemic of the Malaysian National Anthem in Indonesian Mass Media)

Abstract: Indonesia and Malaysia are neighbouring countries in the Southeast Asian region. The geographical position is the opposite of that in Southeast Asia. However, the number of similarities between the two countries does not necessarily make the relations between the two harmonious. After the 2000s, Indonesia-Malaysia relations often underwent ups and downs. The problem of territorial disputes, cultural claims, migrant workers, as well as the fog due to forest and land fires illustrates the ups and downs of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Past studies on bilateral relationship between Malaysia and Indonesia showed that the media and media staff play important roles in mediating the conflict between the two countries. Scattered research on related issue examined media content, roles, framing and news constructions on specific issues such as Ambalat, cultural heritage (batik) and migrant labours (Adnan & Amri, 2016;Bharata & Nik Norma, 2019;Fauziah et al, 2018;Irwansyah, 2017;Mulharnetti, 2015;Rusdi et al, 2013;Wijayani et al, 2012;Wan Hassan et al, 2017) but lack of study on media staff newsroom routine. Media is perceived as powerful medium used by journalists and editors to either alleviate or reduce the rage among fellow nations by highlighting certain story angles repeatedly while excluding others.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies on bilateral relationship between Malaysia and Indonesia showed that the media and media staff play important roles in mediating the conflict between the two countries. Scattered research on related issue examined media content, roles, framing and news constructions on specific issues such as Ambalat, cultural heritage (batik) and migrant labours (Adnan & Amri, 2016;Bharata & Nik Norma, 2019;Fauziah et al, 2018;Irwansyah, 2017;Mulharnetti, 2015;Rusdi et al, 2013;Wijayani et al, 2012;Wan Hassan et al, 2017) but lack of study on media staff newsroom routine. Media is perceived as powerful medium used by journalists and editors to either alleviate or reduce the rage among fellow nations by highlighting certain story angles repeatedly while excluding others.…”
Section: Problem Statementmentioning
confidence: 99%
“…News editor is a powerful force in the newsroom but indistinct figure in academic study. Editors direct the journalists and assess their work; they manage the converged (or otherwise) newsroom; and they decide just how much influence the audience will have -indicating that there is possibility of conflicting interests occur in their everyday routine (Adnan & Amri, 2016;Bharata & Nik Norma, 2019;Skjerdal, 2013;Selo et al, 2015;Wan Hassan et al, 2017). Conflict of interests arise when "contradictory goals and actions of different social subjects lead to a position where the conflict is impossible to avoid" (Soloski, 1989, pp.…”
Section: Introductionmentioning
confidence: 99%